Pengaruh Program Magang, Soft Skill, dan Minat Kerja terhadap Kesiapan Kerja Mahasiswa Indonesia Banking School - Ikraman Wahyudin; Meta Andriani (CV. ALIM'SPUBLISHING, 2026)
Abstract. This study aims to analyze the influence of internship programs, soft skills development, and work interest on the work readiness of students at STIE Indonesia Banking School, Class of 2022. Work readiness is an important aspect that helps students prepare for the transition from higher education to the professional world. This research employed a quantitative approach using data collected through questionnaires distributed to students who had participated in internship programs. A total of 31 respondents were involved in the study, and the data were analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. The results indicate that internship programs and soft skills development have a positive and significant effect on students’ work readiness. Internship experiences provide opportunities for students to gain practical knowledge, understand workplace culture, and develop professional competencies. Meanwhile, soft skills development supports communication, teamwork, leadership, and problem-solving abilities that are needed in the workplace. In contrast, work interest does not have a significant effect on work readiness. These findings suggest that practical experience and soft skills play a more important role in preparing students for employment than work interest alone.